Introducing Culture in EFL Class: The Junior High School Teachers’ Awareness - Astrid, Annisa; Okta Sukma, Fitri Alya; Saputra, Eko; Chairuman, Muhamad Chalik (Institut Agama Islam Negeri Palopo, 2023)
The integration of culture into language teaching, particularly in the English as a Foreign Language (EFL) class, is widely regarded as an essential aspect of English teaching. The objective of this study is to explore the 7th-grade teachers’ awareness of Junior High school on introducing culture in EFL class. The research employed a quantitative survey in 26 junior high schools located in Palembang, South Sumatra. The data were collected from 115 English teachers who responded to a set of questionnaire items. Subsequently, the data underwent analysis by the use of descriptive statistics. The findings revealed that English teachers at the seventh-grade level are aware of incorporating cultural components within the context of English language teaching. To begin with, it is evident that the teachers possess a comprehensive understanding of the significance of culture and context in interpreting meaning. Furthermore, the teachers have a fundamental experience of the significance of being able to analyze and contrast cultures concerning their shared characteristics and distinctions. Thirdly, the teachers widely acknowledge that cultural learning has a predominantly positive influence within the English classroom. In the realm of English teaching, the teachers have a consensus regarding the significance of incorporating cultural learning activities into the classroom setting. Ultimately, junior high school English teachers exhibit a predominantly favorable disposition towards the significance of including cultural learning activities inside the English instructional setting